2004
DOI: 10.1111/j.1349-7006.2004.tb03188.x
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus‐induced, death receptor‐dependent apoptosis and regression of transplanted human cancers

Abstract: he use of replication-competent viral vectors, in particular herpes simplex virus (HSV) type 1 vectors, is a promising strategy for cancer therapy because the virus can replicate and spread in situ, exhibiting oncolytic activity through a direct cytopathic effect.1) A number of oncolytic HSV vectors have been developed by introduction of mutations that disrupt genes associated with neurovirulence and/or viral DNA synthesis in order to restrict viral replication in transformed cells and to diminish the infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Another controversial issue has been to what extent death receptor signalling contributes to HSV-1- and SFV-induced apoptosis. While in one case inhibition of FasL by soluble Fas did not prevent apoptosis caused by HSV [ 46 ], another report found that HSV-induced apoptosis was suppressed by antibodies directed towards Fas or FasL [ 47 , 48 ]. Moreover, gD and gJ of HSV-1 were shown to protect against FasL-induced apoptosis [ 17 , 18 ] and dendritic cells seem to die after HSV-1 infection due to the downregulation of the caspase-8 inhibitor c-FLIP [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another controversial issue has been to what extent death receptor signalling contributes to HSV-1- and SFV-induced apoptosis. While in one case inhibition of FasL by soluble Fas did not prevent apoptosis caused by HSV [ 46 ], another report found that HSV-induced apoptosis was suppressed by antibodies directed towards Fas or FasL [ 47 , 48 ]. Moreover, gD and gJ of HSV-1 were shown to protect against FasL-induced apoptosis [ 17 , 18 ] and dendritic cells seem to die after HSV-1 infection due to the downregulation of the caspase-8 inhibitor c-FLIP [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…So it promoted the transmission of intracellular information. Because that information could be positive or negative signal, consequently, it resulted in cellular growth was inhibited or cellular apoptosis [44], cellular hyperplasia or differentiation, secretion of cytokine, and so on. Wright et al [45] further confirmed that in ALCL cells, the stimulation of CD30 elicits p21 (waf1)-mediated arrest through the canonical but not the alternative NF-kappaB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…First, several members of the death receptor family were induced by anti-apoA-1 antibodies. Among them, TNF receptor super family 8 (TNFRSF8 or CD30) and TNFRSF10D (TRAIL Receptor), together with two TNFRSF ligands TNFSF9 (CD137Ligand) and TNFSF4 (Ox40 Ligand) were notably up-regulated and some link to caspase 3-dependent tumor apoptosis have been described for TNFRSF8 (CD30) [56][57][58] and for TNFSF9 [59,60], the lastest being also involved in promoting neuronal cell death [61]. TLR6, TLR1, TLR10 and CD14, co-receptors of TLR2 and TLR4 previously identified as anti-apoA-1 antibodies receptors [9,13], and TLR4 have been transcriptionnaly up-regulated.…”
Section: Discussionmentioning
confidence: 99%